2014
DOI: 10.1681/asn.2013101143
|View full text |Cite
|
Sign up to set email alerts
|

Translational Profiles of Medullary Myofibroblasts during Kidney Fibrosis

Abstract: Myofibroblasts secrete matrix during chronic injury, and their ablation ameliorates fibrosis. Development of new biomarkers and therapies for CKD will be aided by a detailed analysis of myofibroblast gene expression during the early stages of fibrosis. However, dissociating myofibroblasts from fibrotic kidney is challenging. We therefore adapted translational ribosome affinity purification (TRAP) to isolate and profile mRNA from myofibroblasts and their precursors during kidney fibrosis. We generated and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 49 publications
3
87
1
Order By: Relevance
“…Myofibroblast precursors all generate COL1 protein and other collagen proteins in healthy kidney, but the mechanism of turnover is obscure (16). Recent studies have identified ADAMTS-2 as a highly upregulated gene in FOXD1-lineage cells when they become myofibroblasts, while its endogenous inhibitor TIMP-3 is highly downregulated (42,99,100). ADAMTS-2 cleaves procollagen-I to facilitate fibril formation (101) and may therefore be an important endogenous regulator of matrix turnover in health and disease, whereas TIMP-3 deficiency results in increased matrix deposition in the kidney (42).…”
Section: Resolution Of Fibrosismentioning
confidence: 99%
“…Myofibroblast precursors all generate COL1 protein and other collagen proteins in healthy kidney, but the mechanism of turnover is obscure (16). Recent studies have identified ADAMTS-2 as a highly upregulated gene in FOXD1-lineage cells when they become myofibroblasts, while its endogenous inhibitor TIMP-3 is highly downregulated (42,99,100). ADAMTS-2 cleaves procollagen-I to facilitate fibril formation (101) and may therefore be an important endogenous regulator of matrix turnover in health and disease, whereas TIMP-3 deficiency results in increased matrix deposition in the kidney (42).…”
Section: Resolution Of Fibrosismentioning
confidence: 99%
“…Using transgenic mice for example for the collagen1a1 promoter coupled with the reporter for translating ribosome affinity purification (TRAP), translational profiling of medullary pericytes was performed in healthy and fibrotic kidneys. This approach identified several previously unappreciated and highly regulated genes in fibrosis which are mostly involved in proliferation, cytoskeleton, cell-cell connections and motility (169). Similar genetic approaches allow profiling of various renal cells including fibroblasts, tubular cells, endothelium and monocytes and macrophages (using Foxd1, Six2, Cdh5, or Lyz2 promoters, respectively) and will likely lead to the identification of novel targets in renal fibrosis (38).…”
Section: The Role Of Interstitial Mesenchymal Cellsmentioning
confidence: 99%
“…So far, myofibroblasts have been characterized by their prominent expression of a-smooth muscle actin (aSMA). With the development of novel markers, targeting tools, transgenic mice and cell isolation protocols, the functional and phenotypical heterogeneity and plasticity of these cells is becoming apparent (24,166,167,169). Using transgenic mice for example for the collagen1a1 promoter coupled with the reporter for translating ribosome affinity purification (TRAP), translational profiling of medullary pericytes was performed in healthy and fibrotic kidneys.…”
Section: The Role Of Interstitial Mesenchymal Cellsmentioning
confidence: 99%
“…70 To overcome the challenges in isolating pericyte and myofibroblast-specific RNA, we applied a unique approach called translating ribosome affinity purification. 71 This involves the cell-specific expression of the ribosomal subunit protein L10a fused in-frame to enhanced green fluorescent protein (eGFP).…”
Section: Pericyte Transcriptome After Injurymentioning
confidence: 99%
“…A number of novel secreted proteins may be useful as noninvasive biomarkers of renal fibrosis. 70 The signaling pathways most notably up-regulated include integrin PDGF signaling, and up-regulated gene families include snail homologs as well as the Wnt modulating gene family, secreted frizzled related proteins. These pathways comprise known important regulators of myofibroblast function and kidney fibrosis, providing further internal validation of this approach.…”
Section: Pericyte Transcriptome After Injurymentioning
confidence: 99%